2009
DOI: 10.1016/j.jasms.2008.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence for an oxazolone structure of the b2 fragment ion from protonated tri-alanine

Abstract: Infrared multiple photon dissociation (IRMPD) spectroscopy is used to identify the structure of the b(2)(+) ion generated from protonated tri-alanine by collision induced dissociation (CID). The IRMPD spectrum of b(2)(+) differs markedly from that of protonated cyclo-alanine-alanine, demonstrating that the product is not a diketopiperazine. Instead, comparison of the IRMPD spectrum of b(2)(+) to spectra predicted by density functional theory provides compelling evidence for an oxazolone structure protonated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
119
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 38 publications
(56 reference statements)
5
119
0
Order By: Relevance
“…Table 1 presents the CID mass spectrum of the b 2 ion and compares that with the spectrum of protonated cyclo(Ala-Ala) and with that of the b 2 ion derived by fragmentation of protonated trialanine. Oomens et al [19] have recently shown by infrared multiphoton dissociation (IRMPD) that the latter b 2 ion has an oxazolone structure protonated at the oxazolone N-atom.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the CID mass spectrum of the b 2 ion and compares that with the spectrum of protonated cyclo(Ala-Ala) and with that of the b 2 ion derived by fragmentation of protonated trialanine. Oomens et al [19] have recently shown by infrared multiphoton dissociation (IRMPD) that the latter b 2 ion has an oxazolone structure protonated at the oxazolone N-atom.…”
Section: Resultsmentioning
confidence: 99%
“…Gaskell and coworkers used IM-MS to identify both oxazolone and macrocyclic structures for the b 5 ion from YAGFL-NH 2 , while Clemmer and coworkers used a similar approach to identify linear and macrocyclic structures for the a 4 and b 4 fragment ions from leucine enkephalin [21,22]. Variable wavelength action IRMPD spectroscopy has been recently employed by several research groups for the study of gas-phase ions [23][24][25][26] and has also been the subject of two recent, extensive reviews [27,28]. Action IRMPD spectroscopy is ideal for structural characterization of ions, as the IR spectra generated depict the vibrational modes of selected ions, which can be directly correlated to structural features.…”
mentioning
confidence: 99%
“…Relative energies for all species were calculated by correcting B3LYP/6-311ϩg(d,p) total energies for zeropoint vibrational energy (ZPE) obtained from the unscaled frequencies determined at the same level of theory. Predicted IR spectra were generated at the B3LYP/6-311ϩg(d,p) level of theory and scaled by a factor of 0.98, which is commonly used when comparing DFT and IRMPD data for peptides [29,30,32].…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%
“…Low-energy CID of protonated peptides promotes rearrangement reactions in which the added proton presumably migrates to the amide bond that is ultimately cleaved [1][2][3][4][5][6][7][8][9][10][11][12], as treated in the "mobileproton" (MP) [13][14][15][16][17][18][19][20][21][22][23][24][25], and "pathways in competition" (PIC) models of peptide dissociation [26]. Experimental studies have established that the C-terminus-containing y n ϩ fragments are truncated peptides [6,27,28], while the N-terminus-containing b n ϩ and a n ϩ species have substituted oxazolone ring and imine structures, respectively [4,5,11,12,29,30].Wavelength-selective infrared multiple photon dissociation (IRMPD) spectroscopy has recently been used to probe and confirm proposed structures of peptides and peptide dissociation products, with studies of the latter focusing primarily on b n ϩ and a n ϩ ions [11,12,29,30]. Our group has designed model peptides and approaches to probe intramolecular migration of protons during peptide dissociation reactions [31,32].…”
mentioning
confidence: 99%
See 1 more Smart Citation